Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/v11020128
|View full text |Cite
|
Sign up to set email alerts
|

Angiomotin-Like 1 Links Paramyxovirus M Proteins to NEDD4 Family Ubiquitin Ligases

Abstract: To define the links between paramyxovirus budding and cellular ESCRT machinery, we previously identified angiomotin-like 1 (AMOTL1) in a screen for host factors that bind to the matrix (M) protein of parainfluenza virus 5 (PIV5). This protein harbors three L/PPXY sequences, allowing it to interact with WW domain containing proteins including NEDD4 family members. We hypothesize that paramyxoviruses use AMOTL1 as a linker to indirectly recruit the same NEDD4 ubiquitin ligases for budding that other enveloped vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…One of the key regulators of YAP1 localization and activity is Amot, which binds strongly to the first WW-domain of YAP1 via one of its multiple N-terminal PPxY motifs [84]. Amot, along with other family members, plays an important role in the biology of the vascular system, and Amot has been linked previously to budding of other RNA viruses [85][86][87][88]. Interestingly, we observed a dose-dependent rescue of mVP40 VLP budding when increasing amounts of Amot were added to cells co-expressing mVP40 and either YAP1 or TAZ.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key regulators of YAP1 localization and activity is Amot, which binds strongly to the first WW-domain of YAP1 via one of its multiple N-terminal PPxY motifs [84]. Amot, along with other family members, plays an important role in the biology of the vascular system, and Amot has been linked previously to budding of other RNA viruses [85][86][87][88]. Interestingly, we observed a dose-dependent rescue of mVP40 VLP budding when increasing amounts of Amot were added to cells co-expressing mVP40 and either YAP1 or TAZ.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding paramyxovirus M protein and host protein interactions, it has been reported that the interaction of the Nipah and Hendra virus M proteins with AP3B1 protein promotes virus-like particle (VLP) production [ 33 ]. In addition, the angiomotin-like 1 protein interacts with the parainfluenza virus 5 (PIV5) M protein [ 34 ] and acts as a linker between the PIV5 M and NEDD4 ubiquitin ligases [ 35 ], which reveals a novel host factor recruitment strategy for paramyxoviruses to achieve VLP production and virus budding. Moreover, a recent study showed that annexin A2 interacting with the measles virus (MeV) M protein mediates the plasma membrane localization of the M protein and assists the assembly and budding of progeny virions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This neatly explains why NEDD4-2, which binds to PPXY that HIV lacks, rescues the late domain mutant lacking both PTAP and YPXL domains [ 103 ]. AMOT-1 was also shown to facilitate paramyxovirus budding in a similar manner as it does in HIV [ 108 , 109 ]. However, AMOT-1 (but not the other members of the agiomotin family) is specifically required for bridging the M protein and E3 ubiquitin ligase [ 109 ].…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%